1998
DOI: 10.1007/s004050050045
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic cell separation for purification of human oral keratinocytes: an effective method for functional studies without prior cell subcultivation

Abstract: In studying human oral keratinocytes, it would be very helpful to obtain a pure population of cells without prior in vitro expansion. An immunomagnetic separation technique, or magnetic cell separation (MACS), was modified for efficient purification of human oral keratinocytes. Subsequent to two-step enzymatic digestion, the cell suspension was labelled with a mouse anti-CD45 (pan-leukocyte) monoclonal antibody (MoAb) to stain mononuclear cells. In a second step a rat anti-mouse antibody conjugated with colloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Previous studies showed that MACS enrichment did not alter the viability and functional abilities of different cell types [19]. This corresponds to our own data where oral keratinocytes of different origin showed unaltered cytokine expression before and after MACS [17].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous studies showed that MACS enrichment did not alter the viability and functional abilities of different cell types [19]. This corresponds to our own data where oral keratinocytes of different origin showed unaltered cytokine expression before and after MACS [17].…”
Section: Discussionsupporting
confidence: 74%
“…For purification of oral mucosa-derived human keratinocytes we used an immunomagnetic separation technique (MACS) to avoid further subcultivation [17]. Previous studies showed that MACS enrichment did not alter the viability and functional abilities of different cell types [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enriching of epithelial stem cells is a desirable goal in approaches for tissue engineering of oral mucosa. Many methods exist for facilitating such a separation [18]: nonimmunological methods such as velocity sedimentation [19], and immunological procedures such as fluorescenceactivated cell sorting (FACS) [20], complement lysis [21], rosetting [22], and magnetic cell separation (MACS) [23,24]. These methods are very successful for this purpose but have disadvantages caused by the high degree of physical stress acting on the cells during these procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Separated cells were obtained by using selective enzymatic digestion [4] in conjunction with physical and immunological separation procedures [5]. In vitro procedures, using separated endometrial cell types, present the experimental approach to study the uPA and uPAR expression at the cellular level.…”
Section: In Vitro Expression Of Upa and Upar By Cultured Human Eutopimentioning
confidence: 99%